The Pyruvate Dehydrogenase Complex in Sepsis: Metabolic Regulation and Targeted Therapy - Zeng, Zhenhua; Huang, Qiaobing; Mao, Liangfeng; Wu, Jie; An, Sheng; Chen, Zhongqing; Zhang, Weijin (Frontiers in Nutrition, 2021)
Anaerobic glycolysis is the process by which glucose is broken down into pyruvate and lactate and is the primary metabolic pathway in sepsis. The pyruvate dehydrogenase complex (PDHC) is a multienzyme complex that serves as a critical hub in energy metabolism. Under aerobic conditions, pyruvate translocates to mitochondria, where it is oxidized into acetyl-CoA through the activation of PDHC, thereby accelerating aerobic oxidation. Both phosphorylation and acetylation affect PDHC activity and, consequently, the regulation of energy metabolism. The mechanisms underlying the protective effects of PDHC in sepsis involve the regulation on the balance of lactate, the release of inflammatory mediators, the remodeling of tricarboxylic acid (TCA) cycle, as well as on the improvement of lipid and energy metabolism. Therapeutic drugs that target PDHC activation for sepsis treatment include dichloroacetate, thiamine, amrinone, TNF-binding protein, and ciprofloxacin. In this review, we summarize the recent findings regarding the metabolic regulation of PDHC in sepsis and the therapies targeting PDHC for the treatment of this condition.